Hydrodynamic Characteristics and Sediment Distribution Patterns in Wulan Delta Estuary, Demak, Indonesia - Muskananfola, Max Rudolf; Febrianto, Sigit; Ayuningrum, Diah (Makara Journal of Technology, 2023)
The Wulan Delta, located in Wedung, Demak, was formed due to the sedimentation process of the Wulan and Serang rivers. Sediment transport starts from rivers to the sea; the process carries nutrients and various chemicals derived from agricultural, industrial, or household activities. This study aims to analyze the characteristics of hydrodynamics, suspended sediment, and bottom sediments in the Wulan Delta waters, Demak. Field data were collected in transitional season two (October) 2022. The obtained data were then analyzed in the laboratory at the Faculty of Fisheries and Marine Science. Results showed that the speed of the surface current in the study area ranged from 0 to 0.1 m/s in spring tide conditions with a surface current pattern coming from the direction of Semarang toward Jepara and 0–0.18 m/s in neap tide conditions with a current pattern coming from the direction of Jepara toward Semarang. The Wulan Delta has a sedimentary characteristic dominated by fine silt, which is as much as 82%–98%, with a deposition characteristic dominated by wave energy that causes successful sediment sorting with a sorting index of −2.25 to 2 and strongly asymmetrical to a small size with a skewness curve value of two.